Thermodynamic analysis of the reactions of sulphur containing compounds in the process of diesel fractions hydrodesulphurization on the base of quantum-chemical calculations; Petroleum and Coal; Vol. 61, iss. 1 - Frantsina E. V. Evgeniya Vladimirovna; Krivtsova N. I. Nadezhda Igorevna; Belinskaya N. S. Natalia Sergeevna; Kotkova E. P. Elena Petrovna (2019, 2019)
Title screen